(untitled) (Fiep Bulletin - online, 2014)
Introduction : Aging is a natural process of the human being , which passes through all stages of life from childhood to adulthood , closing the cycle of life , with advancing age, with changes throughout the body , including the skin human . The skin can reveal their chronological age or brake the appearance of old age . The body relaxing massage through its movements as slip , friction , kneading and percussion , providing benefits such as relaxation , increased oxygen supply , reduced muscle tension and pain , decreases anxiety , among many other physiological benefits ( CASSAR , 2001; NESSI , 2010) , due to its influence on various organic processes . Objective: Check through the practice of Body Relaxing Massage in Elderly female population between 60 and 82 years, improvement, prevention and maintaining hydration of the skin of the upper limbs, with the apparatus Corneometer CM 85 PC, the company Tecnotests.Methods : Application of Massage in 05 sessions , 01 once a week with a group of 40 subjects 60-82 years old, female , using techniques of body relaxing massage and neutral cream . Expected to improve the appearance of aging skin through massage on the skin and moisturizing of the upper limbs . Verified by device Corneometer CM 85 PC . Results: We conclude that in all sessions Relaxing Body Massage associated with hydration through Massage Cream Neutral , held in the upper limbs ( upper limbs ) a significant increase was observed in the pH of the skin , where the first session was the average of 69 , 2 and the last 93.75 . The skin aging appears more resected by engagement of the sebaceous glands and sweat glands , making it more susceptible to flaking and abrasions. ( MALAQUIAS ; BACHION ; NAKATANI , 2008; BRITO , 2003) With these data we conclude that the Massage Cream Neutral Relaxing Body Massage associated with movements such as gliding , kneading and friction , has a better absorption with the direct action of the hands over the region massaged , favoring better-looking skin by visual observation and increased skin hydration , with evaluation of cutaneous pH . For Physical Activity , is less risk of injury taking preventive action .